Government Planners and Critical Planning Practices as Allies: Tactics for Socio-Spatial Planning Innovations. - Devos, Tim (Taylor & Francis, 2021)
A co-evolutionary approach has been gaining momentum in planning research and practice. Setting itself apart by going beyond the confines of government, starting from a level playing field, and refusing predefined outputs, it is a situational and relational approach through and through. Arguably, this strand of research has predominantly focused on forms of activism or radical planning taking place outside government-led processes, turning to the concept of self-organisation. This article, however, explores the possibility to reconnect a co-evolutionary approach to forms of contentious action occurring within or on the borderlines of the local government apparatus. In doing so, this article seeks to address an apparent gap when it comes to studying planning activism: forms of contentious actions where governmental actors collaborate with professional planning practices in challenging institutionalised methods, or commonplace procedures and instruments. Based on an analysis of two commissioned planning assignments in which the author was involved, this article aims to identify a set of reoccurring tactics mobilised to bridge social and spatial knowledge within local administrations. It does so by using four navigation techniques that can be deployed in an actor-relational approach (Hillier 2016) as an analytical framework.
Keywords: Planungstheorie; Planungsbegriff; Governance; Selbstorganisation; Kooperationsmodell; Institutionalisierung; Planungspraxis; Wissensbasis; Akteur; Informelle Planung; Fallstudie